Dynamic data reconciliation to enhance the performance of feedforward/feedback control systems with measurement noise. (December 2021) - Zhu, Wangwang; Zhang, Zhengjiang; Chen, Junghui; Zhao, Sheng; Huang, Shipei
Abstract: To inhibit the effect of disturbance in a system, feedforward control is usually combined with feedback loops to provide better control. The working environment for feedforward/feedback control system generally considers the commonly measured or unmeasured external disturbances. However, the Gaussian/non-Gaussian measurement noise from sensors during the measurement process for feedback loops will affects the performance of a control system. This paper proposes dynamic data reconciliation (DDR) filter combined with the feedforward/feedback control system to account for Gaussian/non-Gaussian measurement noises. This reduces the effect of disturbances and Gaussian/non-Gaussian measurement noises on performance. The DDR filter determines the optimal feedback signals using model prediction and measurements. Simulation examples of feedforward/feedback control systems show that the proposed DDR filter enhances performance and gives better filtering than a traditional digital filter. An application case study, which combines a DC–AC​ converter with DDR, is also tested to illustrate the effectiveness of the proposed DDR filter. Highlights: Effect of Gaussian/non-Gaussian disturbances on control performances is analyzed. Dynamic data reconciliation (DDR) is developed to enhance control performances. DDR corrects measurements with Gaussian/non-Gaussian disturbances and noises. SISO, MIMO, and DC–AC converter control systems are used for verification.